Influence of GSM speech coding on the performance of text-independent speaker recognition - Grassi, Sara; Besacier, Laurent; Dufaux, Alain; Ansorge, Michael; Pellandini, Fausto (My University, 2000)
We have investigated the influence of GSM speech coding in the performance of a text-independent speaker recognition system based on Gaussian Mixture Models (GMM). The performance degradation due to the utilization of the three GSM speech coders was assessed, using three transcoded databases, obtained by passing the TIMIT through each GSM coder/decoder. The recognition performance was also assessed using the original TIMIT and its 8 kHz downsampled version. Then, different experiments were carried out in order to explore feature calculation directly from the GSM EFR encoded parameters and to measure the degradation introduced by different aspects of the coder.